Nonlinear Reimbursement Rules for Preventive and Curative Medical Care - Helmuth Cremer; Jean-Marie Lozachmeur (Institute of Labor Economics (IZA), 2024)
We study the design of nonlinear reimbursement rules for expenses on secondary preventive and on therapeutic care. With some probability individuals are healthy and do not need any therapeutic health care. Otherwise they become ill and the severity of their disease is realized and identifies their ex post type. Preventive care is determined ex ante, that is before the health status is determined while curative care is chosen ex post. Insurance benefits depend on preventive and curative care in a possibly nonlinear way, and marginal benefits can be positive or negative. In the first best, achieved when health status is ex post publicly observable, insurance benefits are flat (lump sum payments) and do not depend on expenditures. When the severity of the disease is not observable, so that there is ex post moral hazard, this solution is not incentive compatible (for more healthy individuals). The optimal insurance then implies benefits that increase with both types of care. This is because health expenditures reduce informational rents and they are upward distorted. This relaxes the incentive constraint because less healthy individuals value care more than healthy individuals. Even though preventive care is chosen ex ante, when there is no asymmetry of information, it does have an impact on the incentive constraint and thus on informational rents. This is due to two concurring effects. First, prevention is more eective for the more severely ill. Second, these individuals also have a lower marginal utility of income so that a given level of expenditure on preventive care has less impact on their utility. Finally, when individuals misperceive the benefits of preventive care, our results remain valid, but there is now an extra corrective (Pigouvian) term in the expression for the marginal reimbursement of preventive care.
Keywords: I11; I13; I18; 330; ex post moral hazard; health insurance; secondary prevention